July 15: The glorious resistance of Turkish democracy - Yayla, Atilla (SETA Foundatıon, 2016)
On 15 July 2016, Turkey experienced a milestone in its political history. An entity, judicially and officially recognized as the Gulenist Terror Organization (FETO), operating through a group of its disciples nested in the Turkish military, attempted to overthrow Turkey's legitimate and elected government. Several important and unprecedented factors prevented the coup d'etat. Among them, the determined and courageous approach of the ruling AK Party, in solidarity with its opposition; the heroic resistance of the people of Turkey, the Turkish police, and members of the Turkish armed forces; the anti-coup stance of the judiciary; and the democratic posture of the mainstream media. The foiling of the coup attempt will contribute tremendously to Turkish democracy in many respects. In short, the democracy in Turkey in the post-July 15 period will emerge stronger than ever before.
WOS: 000450370600008
Keywords: Turkey; Foreign Policy; Turkish Democracy